Effectiveness of Laser Acupuncture and Battlefield Acupuncture Therapy for Pain Management in Juvenile Idiopathic Arthritis : A Case Report - Dwi Surya Supriyana; Arsita Eka Prasetyawati; Robby G Sebayang; Kemas Abdurrohim (Faculty of Medicine Universitas Sebelas Maret, 2020)
Introduction : Juvenile Idiopathic Arthritis (JIA) is a comprehensive chronic condition of a joint inflammatory autoimmune process, resulting a decrease of function in a long period characterized by fever and pain, which is include all form of unknown etiology that begin before 16 years old. Here we reported effectiveness of Laser Acupuncture and Battlefield Acupuncture Therapy for pain management in JIA case.Case report : A 10-year-old girl diagnosed with JIA was admitted to the pediatric department in Dr. Cipto Mangunkusumo Hospital, and treated by clinical multidisiplinary team from pediatrict, orthopedist, nutritionist, physiotherapist, and medical acupuncture doctor. She was referred to the Medical Acupuncture Department due to complaining of prolonged continous pain throughout her joints, and swelling in her right knee joint. The patient received laser acupuncture therapy in acupoints LI4 Hegu, LI11 Quchi, ST36 Zusanli, SP9 Yinliquan, and EX-LE5 Xiyan. Battlefield Acupuncture Points method (ears) of Omega2, Shenmen, Gyrus Cingulate, Thalamus, and Point Zero. The Therapy was given every day for two weeks and showed a significant improvement on patient’s Visual Analog Score.Conclusion : The combination regimen was effective in relieving pain and swelling, and caused a significant Visual Analog Score and Range of Motion improvement in our case.